2008
DOI: 10.1007/s10295-008-0377-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lipidic carbon sources on the extracellular lipolytic activity of a newly isolated strain of Bacillus subtilis

Abstract: An isolate exhibiting high extracellular lipolytic activity was identified as Bacillus subtilis by 16S rRNA gene sequence analysis. The enzyme activity of the isolate was improved by using different concentrations of lipidic carbon sources such as vegetable oils, fatty acids and triglycerides. Lipolytic activity was assayed spectrophotometrically using p-nitrophenyl palmitate. One percent (v/v) of sesame oil provided the highest activity with 80 and 98% enhancements with respect to 1% (v/v) concentrations of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Glucose, olive oil, peptone, and FeCl 3 ⋅6H 2 O were found to have more significant influence on lipase production by C. rugosa. Takaç and Marul (2008) improved the lipase production by B. subtilis using different concentrations of lipidic carbon sources such as vegetable oils, fatty acids, and triglycerides. One percent of sesame oil afforded the highest activity with 80% and 98% enhancements with respect to 1% concentrations of linoleic acid and triolein as the favored fatty acid and triglyceride, respectively.…”
Section: Synthetic Mediummentioning
confidence: 98%
See 2 more Smart Citations
“…Glucose, olive oil, peptone, and FeCl 3 ⋅6H 2 O were found to have more significant influence on lipase production by C. rugosa. Takaç and Marul (2008) improved the lipase production by B. subtilis using different concentrations of lipidic carbon sources such as vegetable oils, fatty acids, and triglycerides. One percent of sesame oil afforded the highest activity with 80% and 98% enhancements with respect to 1% concentrations of linoleic acid and triolein as the favored fatty acid and triglyceride, respectively.…”
Section: Synthetic Mediummentioning
confidence: 98%
“…The genes that encode lipase in Candida sp., Geotrichum sp., Trichosporon sp., and Y. lipolytica have been cloned and Bacterial Takaç and Marul (2008) over-expressed (Wang et al 2007). Although lipases from C. rugosa and C. antarctica have been extensively used in different fields, there are several recent publications reporting the production of lipases by other yeasts, as shown in Table 1.…”
Section: Filamentous Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…The fluorescent halo zone surrounding colony was used as an indicator of lipolytic activity [16,17]. The optimum temperature of the growth was determined by culturing the B. subtilis DR8806 in a medium containing 0.5% (w/v) peptone, 0.5% (w/v) yeast extracts, and 3.0% (v/v) olive oil [18]. The medium was incubated under shaking (120 rpm) at 37, 42 and 50 • C for 34 h. The samples were withdrawn at two-hour intervals.…”
Section: Growth Optimization and Enzyme Productionmentioning
confidence: 99%
“…Takaç and Marul [36] showed that the time necessary to reach the maximum activity is dependent on the type of vegetable oil used as supplement. However, an enhancement in fermentation time leads to a drop of lipase activity, independent on the vegetable oil used.…”
Section: Resultsmentioning
confidence: 99%